2022
DOI: 10.26434/chemrxiv-2022-zm0kr
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding How Metal-Ligand Coordination Enables Solvent Free Ionic Conductivity in PDMS

Abstract: Ionically conductive polymers are commonly made of monomers containing high polarity moieties to promote high ion dissociation, like poly(ethylene oxide) (PEO), polyvinylidene difluoride (PVDF), poly(vinyl alcohol) (PVA). However, the glass transition temperature ($T_g$) of these polymers are relatively high, and therefore yields a glassy state at room temperature and limits the mechanical flexibility of the material. Although polydimethylsiloxane (PDMS) has many attractive physical and chemical properties, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 71 publications
(96 reference statements)
1
1
0
Order By: Relevance
“…Meanwhile, the local segmental relaxations and solvation site rearrangements that govern Li + transport are only moderately hindered. While it has been previously shown that total conductivity is unaffected by mixed-salt dynamic network formation, 20 here it is confirmed that Li + conductivity is also unaffected. Furthermore, it is demonstrated here that even a simple dynamic network comprising one type of ligand functionality and two types of metal cations is a straightforward approach to partially decoupling bulk mechanics from Li + conductivity.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Meanwhile, the local segmental relaxations and solvation site rearrangements that govern Li + transport are only moderately hindered. While it has been previously shown that total conductivity is unaffected by mixed-salt dynamic network formation, 20 here it is confirmed that Li + conductivity is also unaffected. Furthermore, it is demonstrated here that even a simple dynamic network comprising one type of ligand functionality and two types of metal cations is a straightforward approach to partially decoupling bulk mechanics from Li + conductivity.…”
supporting
confidence: 79%
“…One dynamic network Li + conductor studied by Mackanic et al 19 uses a hydrogen bonding network to improve toughness and PEO-based backbones to improve conductivity. Similarly, Zhang et al 20 blended a pyridyl amine-functionalized siloxane polymer with Li + and Cu 2+ salts to form a "mixed salt" electrolyte that simultaneously solvates Li + and improves the shear modulus through Cu−pyridyl interactions. More generally, our group has established that conductivity and modulus can be independently tuned via metal−ligand coordination chemistry.…”
mentioning
confidence: 99%